Destruction energy index (DEI) of vitamin E blended UHMWPE for artificial joints. Issue 1 (18th March 2019) - Hatano, Naoya; Higaki, Masaya; Otsu, Youhei; Otsu, Tatsuya; Mikami, Shinji; Matsumoto, Mitsuhiro; Kono, Daisuke; Matsubara, Atsushi; Tomita, Naohide
Abstract : Destruction resistance such as start‐up wear resistance characteristics of vitamin E (dl‐α‐tocopherol) blended ultra‐high molecular weight polyethylene (UHMWPE) were evaluated using the destruction energy index (DEI). The DEI is used to evaluate wear‐like destruction, by minimising the effects of viscosity at the sliding interface, and is estimated using newly designed friction testers. In this experiment, silicone oils of different viscosities were used to determine micro displacement up to a start‐up point, and the DEI of the UHMWPE was changed from 17.48 to 1.84 μJ by adding vitamin E. The results suggest that the blending with vitamin E reduces destruction of UHMWPE at start‐up friction in silicone oils.